Cellulose degradation in the Vasa: The role of acids and rust. (October 2013) - Dedic, Dina; Iversen, Tommy; Ek, Monica
Abstract : The oak timbers of the Swedish warship Vasa are deteriorating. High amounts of oxalic acid have been found along with a low pH and low molecular weight cellulose deep in the wood timbers. The iron-rich surface wood differs from the interior wood in that it displays higher pH and cellulose with higher molecular weight. The objective of this study was to determine why there is a difference in cellulose degradation, pH, and oxalic acid amount between the surface region and the interior of the Vasa timbers. Analysis of cellulose weight average molecular weight by size exclusion chromatography was performed, as well as quantification of oxalic acid and iron by high-performance anion exchange chromatography and atomic emission spectroscopy, respectively. It was found that a decrease in iron content coincides with an increase in oxalic acid concentration and a drop in pH at a certain depth from the wood surface. When iron-rich surface wood samples from the Vasa were mixed with an aqueous solution of oxalic acid, a fast increase of pH over time was observed. Neither interior wood poor in iron nor the fresh oak reference showed the same neutralizing effect during the time of measurement. This indicates that the presence of iron (rust) causes a neutralization of the wood, through the formation of iron(III) oxalato complexes, thus protecting the wood from oxalic acid hydrolysis. This effect was not observed to the same extent for other acids observed in Vasa wood (sulfuric, formic, glycolic, and acetic acids).